Interfacial precipitation and clogging in straight capillaries. (22nd October 2016) - Pal, Sayan; Kulkarni, Amol A.
Abstract: Clogging of straight capillaries during interfacial precipitation (of common salt from saturated salt solution and acetone) was studied for a range of conditions that result in different flow regimes. The particle formation and clogging was explored using the images obtained by tracking a moving slug in real time. The flow regimes varied along the capillary length due to continuous mass transfer of acetone to water resulting in elongation of continuous phase slugs. In the slug flow regime, the precipitated particles formed solid shells/hemi spherical caps at the rear of acetone slugs, which eventually get detached from the interface. In the wavy parallel flow regime, where the interface is not flat, salting out was almost instantaneous and it led to faster clogging of the channels. Smaller Ca, i.e. lower flow rates or the use of smaller capillary length or using continuous fluid of relatively higher viscosity or lower interfacial tension can help to avoid or delay clogging. Formation of cohesive shells at the rear of a slug delayed clogging in the capillaries by delaying settling of individual particles. Parallel flow regime with a flat interface delayed the clogging significantly due to poor mass transfer as well as higher superficial velocities. Highlights: Clogging of straight capillaries during interfacial precipitation was studied. The interfacial precipitation system comprised of saturated salt solution and acetone. A wide range of flow regimes were observed and corresponding clogging time was monitored. Individual slugs were tracked in real time and the dynamics of precipitation were monitored. In slug flow regime, solid shells were observed at the rear end of acetone slugs.